Biosystematics of Angulitermes dehraensis in the Northwestern Indomalayan region by integrating morphometrics and distributional data with DNA barcoding - Lv, Xiuhua; Zhang, Xiaoxia; Azad, Rashid; Zaman, Maid (Frontiers in Insect Science, 2025)
Termites are eusocial and economically important insects which are found in the world’s tropical regions as a harmful or beneficial organism. They play a dual role, both as pests damaging crops and urban structure and as an ecological engineer sustaining the ecosystem. Pakistan is part of the Indomalayan realm hosting diverse flora and fauna including termites; however, the status (diversity, distribution, feeding hosts, pest and non-pest) of the genus Angulitermes in the northwestern region (Khyber Pakhtunkhwa, Pakistan) has been largely neglected. Termite cultures were collected from diverse ecosystems, cleaned, and preserved in alcohol-filled vials for subsequent morphometric identification and DNA barcoding. Coordinates with relevant ecological data were also recorded. Soldiers were used for capturing refined images and morphometric identification through available literature, which resulted as an Angulitermes dehraensis and a new locality record. A revised and updated world’s species list for the genus was made along with the distribution map of this study via ArcGIS. The identified representative soldier’s leg was processed for mtDNA extraction followed by amplification and sequencing. The received sequence was subjected to BLASTn search, and only top 15 sequences via BLASTn search and then via manual search for taxon Angulitermes were retrieved from GenBank. Aligned and trimmed sequences were processed for phylogenetic tree (neighbor-joining and maximum-likelihood) construction and validation of understudy species sequence analogy. A novel sequence was submitted to GenBank for accession number (PX423737). Based on the available and recorded feeding host substrate data, it is a pest species which needs management.